TINJAUAN YURIDIS TERHADAP IJAZAH SEBAGAI OBJEK JAMINAN DALAM PERJANJIAN KERJA ANTARA PERUSAHAAN DAN TENAGA KERJA KONTRAK DI KOTA PEKANBARU - Syusnia Rahmah; Firdaus '; Hayatul Ismi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
The employment’s agreement has great benefits for the parties who entered into this agreement. This should be aware because an employment’s agreement made and adhered to properly will be able to create a job calm, guarantee the certainty of rights and obligation. In fact, the company entered into an agreement but did not comply with labor laws and labor regulations. the company keeps the certificate of diploma as a guarantee outside the agreement. As well as the implementation of agreements that are inconsistent with Undang- undang Nomor 13 Tahun 2013 about Employment.The objective of this thesis is to know applying of diploma as work guarantee on employment’s agreement between companies and contract labor. And to know employment’s agreement which made by companies have complied the provisions that applied of the employments of law. The type of this research were Normative Juridical Research. This research is a research on legal synchronization. In this research, the writer was used Library research. The research was carried out in Pekanbaru. The data source was using primary data, secondary data, and tertiary data. The writer was collected the data by using various libraries, printed mass media, and internet media.There was two problems that can be summarized. First, the content employment’s agreement of PT. Elge Hafil Perkasa with contract labor did not include a certificate of diploma as an assurance but the certificate of diploma is held with a letter of evidence which given to the contract labor as evidence that diploma was held by the company. Whereas, the circular letter’s labor of Pekanbaru City No. Naker/C.4/565/461/IV/2016, dated on April 26th , 2016, contains the prohibition of detention of diploma by private companies, BUMN, BUMD, and Institution did not hold back the certificate of diploma, BPKB, original STNK, and similar goods. The company also make a employment’s agreement that is only one duplicate which held by the company. So the employees do not have employment’s agreement that should be made 2 duplicates that listed in chapter 54, paragraph 3 of Undang-undang Nomor 13 Tahun 2013 about Employment. Second, less supervision of the labor service and less understanding because of the labor agreement by the labor itself. And also less of sanctions for companies that violate the rules established by law and related agencies so there are still many companies that do the same mistake. The writer’s suggestion, first, the company is expected the implement the employment’s agreement in accordance with labor legislation and labor office rules Pekanbaru City. Second, If the company commits a violation then there must be firm sanctions for the company, not just to give a warning letter. So it does not seem to be one-sided about legal matters as well as government supervision on job implementation after the signing of the employment’s agreement, because the company could make mistakes in the execution of the work.Keywords: Employment’s Agreement, Certificate of Diploma, Company